LEVEL OF UNDERSTANDING OF PREPARATION OF FINANCIAL REPORTS FOR MSME IN PARI CITY VILLAGE, PANTAI CERMIN DISTRICT, SERDANG BEDAGAI REGENCY - Dwilita, Handriyani; Sari, Pipit Buana (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This study aims to describe the level of understanding of respondents (MSME business) on financial reports to predict business continuity. The research was conducted in Village 10, Pari City, Pantai Cermin, Serdang Bedagai. This type of research is descriptive qualitative research. Data collection techniques using semi-structured interviews. The results of the study revealed that the level of understanding of the respondents was at the first level, namely knowing. Respondents do not understand or have the ability to explore the process of preparing financial statements. However, at the point of understanding the financial statement accounts, the respondents knew and were able to provide an overview of some of these accounts.